Evangelicals at a Crossroads Revivalism and Social Reform in Boston, 1860-1910. - Hartley, Benjamin L. (Hanover : University of New Hampshire Press, 2011)
The story of Boston revivalism and social reform.
Print version record.
Keywords: Evangelicalism -- Social aspects -- Massachusetts -- Boston -- History -- 19th century; Church and social problems -- Massachusetts -- Boston -- History -- 19th century; Revivals -- Massachusetts -- Boston -- History -- 19th century; Boston (Mass.) -- Church history -- 19th century; Boston (Mass.) -- Social conditions -- 19th century; Boston (Mass.) -- Church history -- 19th century; Boston (Mass.) -- Social conditions -- 19th century; Church and social problems -- Massachusetts -- Boston -- History -- 19th century; Evangelicalism -- Massachusetts -- Boston -- History -- 19th century; Evangelicalism -- Social aspects -- Massachusetts -- Boston -- History -- 19th century; Revivals -- Massachusetts -- Boston -- History -- 19th century; RELIGION -- Christianity -- History; Church and social problems; Evangelicalism -- Social aspects; Revivals; Social conditions; Massachusetts -- Boston; 1800 - 1899; Electronic books; Church history; History